A case of dupilumab‐induced psoriasis‐like eruption treated with baricitinib - Yuki Kinoshita; Hisayoshi Imanishi; Tomoko Oshimo; Daisuke Tsuruta (Wiley, 2024)
Abstract Dupilumab is a humanized monoclonal antibody against the interleukin (IL)‐4 receptor alpha chain that inhibits IL‐4 and IL‐13 signalling. It is one of the systemic treatments for patients with moderate‐to‐severe atopic dermatitis (AD), which provides favourable safety and efficacy. We report a case of psoriasis‐like eruption induced by dupilumab as an adverse effect in a patient with AD, immediately remitted after switching to baricitinib, which inhibits JAK1/2. Moreover, the atopic skin lesion also simultaneously went into remission upon baricitinib treatment. Baricitinib could be a favourable option for patients with AD who develop dupilumab‐induced psoriasis‐like eruption.